“Evaluación de efecto de cuatro dosis de microorganismos eficientes em-1 sobre la incidencia y severidada de nefermedades en el cultivo de cebolla china (allium fistolosum L) en Lamas” - Ríos Alarcón, Lilia (2015)
This paper titled "Evaluation of the effect of four doses of efficient microorganism EM- 1 on the incidence and severity of disease in growing green onion (Allium fistolosum), aimed to Lamas. Evaluating the most efficient dose for the control of microorganisms on the incidence and severity of disease in the cultivation of green onion (Allium fistolosum) Lamas with 4 doses applying microorganisms efficiently EM-1. This research was conducted from March to April 2014 block design was completely randomized, with 4 treatments anda control and 4 blocks .The results we obtained indicate that plant height T2 (3.1-1 .has MBA). with the highest average with T4 others 34, 1cm (33.4 cm), T3 (32,4cm), T1 (31,0cm) and TO (30,7cm) treatments, average plant weight were obtained T 4 (5.1. ha -1 MBA) and T3 (4.1 ha -1 MBA), statistically equal to each other with 42.4 g and 37.4 g, incidence of attack bulbs leaf and roots increased incidence obtained TO (control), with 4.49% outperforming others who obtained treatment T1 (2.46%), T2 (1.45%), T3 (1.0%), T4 (0.06%), the largest attack severity bulbs, leaves, roots is statistically TO with 3.48% outperforming others who obtained treatment T1 (0.56%), T2 (0.06%), T3 (0.06%), T4 (0.06%), respectively .. Keywords: onion, Chinese, EM-1, microorganism, efficient, incidence, severity, diseases